1990
DOI: 10.1037/0097-7403.16.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Conditional discrimination learning by pigeons: The role of simultaneous versus successive stimulus presentations.

Abstract: Three experiments explored the issue of selective associations in the observational conditioning of fear. Experiment 1 results indicated that observer rhesus monkeys acquired a fear of snakes through watching videotapes of model monkeys behaving fearfully with snakes. In Experiment 2, observers watched edited videotapes that showed models reacting either fearfully to toy snakes and nonfearfully to artificial flowers (SN+/FL-) or vice versa (FL+/SN-). SN+/FL- observers acquired a fear of snakes but not of flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…However, our results show that infants do not use social information alone, but also take into account other relevant contextual information—in this case, the kind of object acted upon. This type of selective social learning has been demonstrated before (e.g., Barrett & Broesch, 2012; Cook & Mineka, 1990; DeLoache & LoBue, 2009), and is similar to classic cases of prepared learning (Garcia & Koelling, 1966; Seligman, 1970), but to our knowledge, this is the first demonstration that human infants apply selective inferences to social information about edibility.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, our results show that infants do not use social information alone, but also take into account other relevant contextual information—in this case, the kind of object acted upon. This type of selective social learning has been demonstrated before (e.g., Barrett & Broesch, 2012; Cook & Mineka, 1990; DeLoache & LoBue, 2009), and is similar to classic cases of prepared learning (Garcia & Koelling, 1966; Seligman, 1970), but to our knowledge, this is the first demonstration that human infants apply selective inferences to social information about edibility.…”
Section: Discussionsupporting
confidence: 81%
“…Given that humans have relied on gathered plant resources throughout our evolutionary history, coupled with the costs of trial and error learning, we hypothesized that humans may possess selective social learning strategies that rapidly identify edible plants. Such strategies may operate in similar manner to established cases in which social information is preferentially tied to certain types of entities (e.g., learning about danger; Barrett & Broesch, 2012; Cook & Mineka, 1990; DeLoache & LoBue, 2009). To test this, we examined whether infants would preferentially identify a plant, relative to an artifact, as a food source after they see an adult place both entities in his mouth.…”
mentioning
confidence: 96%
“…Experiment 2 demonstrated that the frequent switching between boxes in Phase 1, designed to invalidate any differences between them as potential retrieval cues, had no noticeable effect on the size of the context-specificity effect. Thomas and Goldberg (1985) had previously shown no significant effect of frequent switching between houselight and tone versus no-houselight and white-noise context, but Thomas et al (1990) and Thomas et al (1987) had shown that frequent switches are essential to establish conditional control by some less salient contextual stimuli. This suggests that the box cues, signaling different locations in the world, are extremely salient to pigeons, despite the fact that the actual cues utilized are not apparent to human observers.…”
Section: Methods Subjects and Apparatusmentioning
confidence: 99%
“…It is well established that conditional discrimination training may be facilitated by providing subjects with frequent and repeated alternations of conditional cues (see Thomas, Cook, & Terrones, 1990;Thomas, Stengel, Sherman, & Woodford, 1987), and in the case of cues that are not very salient, such alternations may be essential. Experiment 2 was performed to test the role of frequent switches between chambers in the initial phase of training.…”
Section: Apparatusmentioning
confidence: 99%
“…The acquisition of contextual control of the F-P and the F-N discriminations in 2 birds (All and F33) after separate training on the two discriminations suggests that the within-session trial-by-trial alternation of contexts that had been used in the original training might have produced interference between trials and prevented the establishment of contextual control (see Thomas, Cook, & Terrons, 1990;Thomas & Goldberg, 1985). However, the 3rd bird (HI2) failed even with separate training on the two discriminations, and the F-N discrimination of F33 was improved after the original within-session trial-bytrial alternation method was rearranged.…”
Section: H12mentioning
confidence: 99%